The Structural, Biophysical, and Antigenic Characterization of the Goose Parvovirus Capsid - Korosh Jabbari; Mario Mietzsch; Jane Hsi; Paul Chipman; Jianming Qiu; Robert McKenna (Microorganisms)
Goose parvovirus (GPV) is an etiological agent of Derzsy’s disease, afflicting geese and Muscovy ducks worldwide. Its high mortality rate among goslings and ducklings causes large losses to the waterfowl industry. Toward molecular and structural characterization, virus-like particles (VLPs) of GPV were produced, and the capsid structure was determined by cryogenic electron microscopy (cryo-EM) at a resolution of 2.4 Å. The capsid exhibited structural features conserved among parvoviruses, including surface two-fold depressions, three-fold protrusions, and five-fold channels. A structural comparison of the GPV viral protein (VP) structure with other adeno-associated viruses (AAVs), including human AAV2, AAV5, and quail AAV (QAAV), revealed unique conformations of several surface-accessible variable regions (VRs). Furthermore, the GPV capsid was found to be thermally stable at physiological pH, but less so under lower pH conditions. As a member of the genus Dependoparvovirus, GPV could also be bound by cross-reactive anti-AAV capsid antibodies that bind to the five-fold region of the viruses, as shown by native immuno-dot blot analysis. Finally, the GPV VP structure was compared to those of other bird dependoparvoviruses, which revealed that VR-III may be important for GPV and Muscovy duck parvovirus (MDPV) infection.